2021
DOI: 10.3390/pathogens10040440
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Subclinical Haemoproteus columbae Infection on Farmed Domestic Pigeons from Central Java (Yogyakarta), Indonesia, with Special Reference to Changes in the Hemogram

Abstract: Pigeon haemoproteosis caused by Haemoproteus columbae (Apicomplexa: Haemosporida: Haemoproteidae) is globally prevalent in rock doves (Columba livia), although little is known regarding this disease in pigeons and doves in Indonesia. Blood samples of 35 farmed domestic pigeons (C. livia f. domestica) from four localities in Yogyakarta Special Region, Central Java, Indonesia, were collected from March to June, 2016, subjected to a hemogram, and analyzed for the presence of hemoprotozoan infections. Microscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
1
4
1
Order By: Relevance
“…A high frequency of infection with HAECOL1 relative to other haplotypes was observed in this study, which is similar to previous findings in wild or domestic pigeons ( Cepeda et al, 2019 ; Chagas et al, 2016 ; Nebel et al, 2020 ; Rosyadi et al, 2021 ; Yumoto et al, 2021 ). Notably, COLIV03 and COQUI05 had minor infection rates ( Nebel et al, 2020 ; Rosyadi et al, 2021 ), consistent with those reported previously. The presence of all three haplotypes has been reported around the world, including the current finding in Thailand ( Table 1 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A high frequency of infection with HAECOL1 relative to other haplotypes was observed in this study, which is similar to previous findings in wild or domestic pigeons ( Cepeda et al, 2019 ; Chagas et al, 2016 ; Nebel et al, 2020 ; Rosyadi et al, 2021 ; Yumoto et al, 2021 ). Notably, COLIV03 and COQUI05 had minor infection rates ( Nebel et al, 2020 ; Rosyadi et al, 2021 ), consistent with those reported previously. The presence of all three haplotypes has been reported around the world, including the current finding in Thailand ( Table 1 ).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, wild pigeons had a 27.6% infection rate with haemosporidian parasite ( Table 1 ), which was similar to the relatively low prevalence rates reported for domestic pigeons in Iran ( Adinehbeigi et al, 2018 ; Dehghani Samani et al, 2013 ) and wild pigeons in Japan ( Yumoto et al, 2021 ). However, the rate of haemosporidian parasite infection can be higher — especially in urban areas or pigeon farms — such as the >95% prevalence in urban areas of South Africa ( Nebel et al, 2020 ) and 65%–100% in pigeon farms in Indonesia ( Rosyadi et al, 2021 ). This difference infection rate is likely associated with population density and habitat area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison with the International Nucleotide Sequence Databases using the BLAST program showed 100% identity with the haplotype HAECOL1 (Accession no. KU131583), which is reported in C. livia from a wide range of tropical and subtropical areas [ 3 , 6 , 12 , 13 ].…”
mentioning
confidence: 99%
“…Anemia is an acknowledged symptom caused by Haemoproteus parasites, with the gametocytes developing in the erythrocytes [ 4 , 5 ]. However, the exo-erythrocytic development, which occurs in different organs, was initially assessed to be less harmful for their avian hosts compared with that of haemosporidian parasites of the genera Plasmodium and Leucocytozoon [ 6 ], and research on Haemoproteus tissue stages remained scarce.…”
Section: Introductionmentioning
confidence: 99%